2018
DOI: 10.1016/j.cell.2018.07.048
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Maintaining Gut Macrophages Are Essential for Intestinal Homeostasis

Abstract: Macrophages are highly heterogeneous tissue-resident immune cells that perform a variety of tissue-supportive functions. The current paradigm dictates that intestinal macrophages are continuously replaced by incoming monocytes that acquire a pro-inflammatory or tissue-protective signature. Here, we identify a self-maintaining population of macrophages that arise from both embryonic precursors and adult bone marrow-derived monocytes and persists throughout adulthood. Gene expression and imaging studies of self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
516
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(586 citation statements)
references
References 43 publications
23
516
2
2
Order By: Relevance
“…They have different phenotypic and functional features related to the needs of the microenvironment. 21 We did not find differences in immune cell counts between symptomatic and asymptomatic patients. This suggests that mucosal low-grade inflammation is merely associated with the presence of diverticula but not symptoms.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…They have different phenotypic and functional features related to the needs of the microenvironment. 21 We did not find differences in immune cell counts between symptomatic and asymptomatic patients. This suggests that mucosal low-grade inflammation is merely associated with the presence of diverticula but not symptoms.…”
Section: Discussionmentioning
confidence: 46%
“…These cells arise from both embryonic precursors and adult bone marrow‐derived monocytes and persist throughout adulthood. They have different phenotypic and functional features related to the needs of the microenvironment …”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence in mice indicates that a separate population of CCR2‐independent intestinal macrophages exists in the gut; these are long‐lived cells that express the markers Tim4 and CD4 . These macrophages are present perinatally and play an essential role in intestinal physiology . Although definitive markers of intestinal macrophage turnover in humans have not been found, a similar hierarchy of subsets may exist in humans .…”
Section: Intestinementioning
confidence: 99%
“…29 These macrophages are present perinatally and play an essential role in intestinal physiology. 30 Although definitive markers of intestinal macrophage turnover in humans have not been found, a similar hierarchy of subsets may exist in humans. 31 Homing of monocytes to the intestine has been proposed to be driven by inflammatory antigens originating from the diet, infection or the commensal microbiota but requirements differ depending on the setting.…”
Section: Origins and Functions Of Macrophages In The Intestinementioning
confidence: 99%
“…Recent studies revealed that monocyte-derived lamina propria macrophages comprise in mice two populations, i.e. short-lived cells and long-lived cells with self-renewing capacity 10 ; the latter population might also include remnants of embryonic populations, as could additional intestinal long-lived macrophage populations that reside near blood vessels, nerves and in the Peyer's patches 11 . Evidence for macrophages with different half-lives is also emerging for the human small intestine 12 .…”
Section: Introductionmentioning
confidence: 99%